2021
DOI: 10.1107/s2053229621002187
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure refinements of stoichiometric Ni3Se2 and NiSe

Abstract: Single crystals of Ni3Se2 (trinickel diselenide) and NiSe (nickel selenide) with stoichiometric chemical compositions were grown in evacuated silica-glass tubes. The chemical compositions of the single crystals of Ni3Se2 and NiSe were determined by scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM/EDS). The crystal structures of Ni3Se2 [rhombohedral, space group R32, a = 6.02813 (13), c = 7.24883 (16) Å, Z = 3] and NiSe [hexagonal, space group P63/mmc, a = 3.66147 (10), c = 5.35766 (16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Laurite–erlichmanite minerals form at a very high temperature (~1250°C; Brenan and Andrews, 2001). Our synthetic experiments without flux under vacuum conditions (Unoki et al , 2021; Yoshiasa et al , 2021) indicated that RuS 2 and RuSe 2 crystals did not melt nor grow, even at 1300°C.…”
Section: Resultsmentioning
confidence: 83%
“…Laurite–erlichmanite minerals form at a very high temperature (~1250°C; Brenan and Andrews, 2001). Our synthetic experiments without flux under vacuum conditions (Unoki et al , 2021; Yoshiasa et al , 2021) indicated that RuS 2 and RuSe 2 crystals did not melt nor grow, even at 1300°C.…”
Section: Resultsmentioning
confidence: 83%
“…This is slightly longer than observed Ni-Se and Ni-Sb distances of 2.469(3) and 2.579(3) Å, respectively. Considering Ni-Se distances, slightly longer NiSe separations of 2.503 Å were observed in synthetic NiSe (Unoki et al, 2021), an analogue of sederholmite, which adopts a nickeline-type structure. Ullmanite shows a Ni-Sb distance of 2.563 Å (Foecker and Jeitschko, 2001) which can be compared with the Ni-Sb separations in the kvačekite structure (2.579(3) Å).…”
Section: Crystal Structurementioning
confidence: 98%